Case Report: Two Patients With EGFR Exon 20 Insertion Mutanted Non-Small Cell Lung Cancer Precision Treatment Using Patient-Derived Xenografts in Zebrafish Embryos - Wang, Qian; Wang, Wenxian; Pan, Weiwei; Lv, Xiaojing; Zhang, Lei; Zheng, Kaiming; Tian, Fang; Xu, Chunwei (Frontiers in Oncology, 2022)
Background: Epidermal growth factor receptor (EGFR) exon 20 insertion mutations are uncommon EGFR mutations and generally resistant to first- and second-generation EGFR-tyrosine kinase inhibitors (TKIs). In precision oncology, treatment regimens are being pursued for predicting a clinical response. Zebrafish embryo tumor transplant models are used in cancer research. Methods: We report two Chinese females who were diagnosed with stage IV lung adenocarcinoma and shown to harbor EGFR exon 20 insertion mutations by next-generation sequencing (NGS). Then, we established lung cancer patient-derived xenografts using a zebrafish model. Zebrafish were inoculated with tumor cells and placed in the culture medium containing the third-generation EGFR-TKI, osimertinib. Fluorescence microscope photographs were used to record the red fluorescence area, which represented the proliferation and migration of tumor cells in the zebrafish. Results: Case one was diagnosed with lung adenocarcinoma (cT4N3M1b, stage IVB) and had an EGFR exon 20 mutation (p. N771delinsHH [abundance 14.08%]). Tumor cell proliferation and migration were significantly reduced in the osimertinib group compared with the control group. The patient received first-line osimertinib (160 mg). According to RECIST v1.1, she achieved a partial response. Case two had stage IVA lung adenocarcinoma with a pleural effusion. The pleural effusion sample was selected to obtain tumor cells for injection, and the zebrafish lung cancer model was established. The proliferation of tumor cells in the osimertinib group was significantly reduced compared to the control group. The migration of tumor cells was not significantly reduced compared to the control group. The patient also received first-line osimertinib (160 mg). The lung lesions were stable, but the pleural effusion was poorly controlled. Conclusion: Our study demonstrated the applicability of a zebrafish embryos model as an innovative platform to targeted drug testing. More precise methods are needed to select treatment options in the future.